Cherchell, Algerien. Die Neuordnung des Nationalmuseums - Dally, Ortwin; Kreilinger, Ulla (e-Forschungsberichte des DAI, 2019)
Since 2008, as part of an Algerian-German cooperation project the National Museum of Cherchell – ancient Caesarea Mauretaniae located on the north coast of Algeria – received a fundamental reorganization, which was supported by the German Department of State. In 2019, the museum, which has been existing for 110 years, is to be reopened, with all the statues presented on new limestone bases in an order structured according to historical criteria, clearly illustrated by panel texts and object captions.